Effect of Dietary Wheat Screening Diet on Broiler Performance, Intestinal Viscosity and Ileal Protein Digestibility - Saki, A.A.; Alipana, A. (International Journal of Poultry Science, 2004)
Much more effort has been made to find out a new source of feed for domestic animal particularly in monogastric and in specific animal such as poultry for their competition by human. Wheat screening (W. S.) is one of best occasion in this respect. The experiment was conducted by 320 day old unsexed Ross 308 chicken, Four rations were used as a four treatments includes (0, 10, 20 and 30%) of wheat screening in broiler diets. Four replicates with 20 birds were arranged in each. Isoenergeytic and netrogenic have modulated in all rations. The experiment was started from 21 days of age to the slaughter weight. Experiment statistical was in complete random design (CRD), data analysed by SAS programme and means were examined by Dancan multiple test. No significant differences were found in body weight (BW), feed intake (FI) and feed conversion ratio (FCR) in 28, 35, 42 and 46 day old chicken by different levels of wheat screening. The similar trend were observed in organelles weight with exception in intestinal and gastrointestinal empty weight and intestinal length which were significantly higher (p<0.05) in 30% of wheat screening (48.09, 266.28 g and 199.12 cm) respectively compared with the control and 10% W.S. ration. In addition Ileal protein and fat digestibility significantly reduced (P<0.05) by 30% wheat screening (78.79 and 68.94%) respectively compared to other treatments. In contrast intestinal viscosity was in the highest significant rate (P<0.05) 1.61 Centipoise (cP) by 30% wheat screening compared with other treatments (1.51, 1.52 and 1.53 cP). The results of this study have shown that there is no any adversely effect of wheat screening on broiler performance. It would suggested that 20% of wheat screening in broiler ration could leads to decrease the ration price and approach more benefits for poultry industry.